The Relationship of Fiber Cell Wall Ultrastructure to Soft Rot Decay in Kempas (Koompassia malaccensis) Heartwood - Singh, A.P.; Wong, Andrew H.H; Yoon, Soo Kim; Seung, Gon Wi (IRGWP, 2004)
The ultrastructure of fiber walls in kempas (koompassia malaccensis) heartwood was examined in relation to soft rot cavity formation. The fibers consisted of middle lamella and thick secondary wall. The secondary wall was differentiated in to a S1 layer, and a unique multi-lamellar S2 layer. Two distinct forms of lamellae were recognisable, one type being considerably thicker than the other. They also differed in their electron density, the thin lamellae being much denser than the thick lamellae. It was not possible to determine whether a S3 layer also existed, because of the presence of a dense material coating the lumen wall, which obscured the definition of this region of the fiber wall. The resistance to soft rot varied with different regions of the fiber wall, middle lamella being completely resistant and the thick S2 lamellae least resistant. The observed relationship between the ultrastructure of these fiber wall regions and the degree of their resistance/susceptibility to soft rot cavity formation is discussed.